Internationalization of Healthcare Applications: A Generic Approach for PACS Workstations - Hussein, R.; Engelmann, U.; Schroeter, A.; Meinzer, H. P. (Methods of Information in Medicine, 2004)
Objectives: Along with the revolution of information technology and the increasing use of computers worldwide, software providers recognize the emerging need for internationalized, or global, software applications. The importance of internationalization comes from its benefits such as addressing a broader audience, making the software applications more accessible, easier to use, more flexible to support and providing users with more consistent information. In addition, some governmental agencies, e.g., in Spain, accept only fully localized software. Although the healthcare communication standards, namely, Digital Imaging and Communication in Medicine (DICOM) and Health Level Seven (HL7) support wide areas of internationalization, most of the implementers are still protective about supporting the complex languages. This paper describes a generic internationalization approach for Picture Archiving and Communication System (PACS) workstations.Methods: The Unicode standard is used to internationalize the application user interface. An encoding converter was developed to encode and decode the data between the rendering module (in Unicode encoding) and the DICOM data (in ISO 8859 encoding). An integration gateway was required to integrate the inter-nationalized PACS components with the different PACS installations. To introduce a pragmatic example, the described approach was applied to the CHILI PACS workstation.Results: The approach has enabled the application to handle the different internationalization aspects transparently, such as supporting complex languages, switching between different languages at runtime, and supporting multilingual clinical reports.Conclusions: In the healthcare enterprises, internationalized applications play an essential role in supporting a seamless flow of information between the heterogeneous multivendor information systems.
Keywords: Internationalization (abbreviated as i18n); DICOM Structured Reporting (SR); DICOM Content Mapping Resource (DCMR); PACS; teleradiology